PEMBERDAYAAN HAK KONSUMEN ATAS INFORMASI OBAT - Sari, Norma (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
This research aims to investigate and identify the empowerment of consumer rights on drug information. Research questions focused on how the role of the Food and Drug Supervisory Agency (BPOM) and pharmacists in the empowering consumers on drug information. Research indicates very important information for consumers in taking the medication. Basic settings need to be protected and fulfilled people the right to information is the Constitution of the Republic of Indonesia in 1945 under Article 28F, Articles 7 and 8 of Law No. 36 of 2009 on, and Article 4 of Law No. 8 of 1999 on Consumer Protection Act. Implementing rules and derivatives can be found in the Decree of the Minister of Health No. 1197 / Minister of Health / SK / X / 2004 on Standards of Pharmaceutical Services in Hospitals and Organizational Rules Number 004 / PP.IAI / 1418 / VII / 2014 about the Organization Regulations Concerning Guidelines for Discipline Pharmacist Indonesia Chapter IV. The right to information is also related to the basic rights of Human Rights.The conclusions showed that the agencyâs role in empowering consumers POM top right drug information is by monitoring the promotion / advertising and labeling of drugs, Communication, Information, Education and Communication (IEC) and formed a Consumer Complaints Service Unit. While the pharmacistâs role on the self medication drug at the pharmacy and hospital pharmacists, by providing information, counseling, promotion and education.